1999
DOI: 10.1001/archinte.159.12.1322
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding During Warfarin and Aspirin Therapy in Patients With Atrial Fibrillation

Abstract: Fixed mini-dose warfarin and aspirin alone or in combination were associated with both minor and major bleeding. The small number of major bleeding events in patients receiving adjusted-dose warfarin therapy as compared with those receiving less intensive antithrombotic treatments and the finding of no significant influence of age on the risk for bleeding indicate that even elderly patients with atrial fibrillation tolerate adjusted-dose warfarin therapy (INR, 2.0-3.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1
12

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(163 citation statements)
references
References 39 publications
(33 reference statements)
4
146
1
12
Order By: Relevance
“…Bleeding is the most common side effect of warfarin and occurs in up to 41% of patients treated with warfarin, with rates of major bleeding in practice of about 7 -8% per year [14,15]. Although major bleeding is of substantial concern, even minor bleeding can lead to withdrawal of therapy [15], thus depriving patients of the most effective, and often only, therapy available to prevent thromboembolism.…”
Section: Narrow Therapeutic Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Bleeding is the most common side effect of warfarin and occurs in up to 41% of patients treated with warfarin, with rates of major bleeding in practice of about 7 -8% per year [14,15]. Although major bleeding is of substantial concern, even minor bleeding can lead to withdrawal of therapy [15], thus depriving patients of the most effective, and often only, therapy available to prevent thromboembolism.…”
Section: Narrow Therapeutic Indexmentioning
confidence: 99%
“…Although major bleeding is of substantial concern, even minor bleeding can lead to withdrawal of therapy [15], thus depriving patients of the most effective, and often only, therapy available to prevent thromboembolism. Minor bleeding also leads to repeat office visits and sometimes emergency room visits.…”
Section: Narrow Therapeutic Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Lechat et al found that there was no statistical difference between the groups for the primary endpoints, but haemorrhagic complications were significantly more frequent in the aspirin group [8]. Gullov et al found in the AFASAK 2 trial that fixed-minidose warfarin and aspirin alone or in combination were associated with both minor and major bleeding [7]. In a recent study with 3,566 patients with chronic AF, receiving warfarin therapy targeted to achieve an INR of 2.0-3.0, patients who were receiving concomitant aspirin (100 mg/ day) had a more than 2-fold increased risk for major bleeding [10].…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…22 Sensitivity analyses in the current study show that variation in the severity and likelihood of the side effects for individual patients has an effect on treatment choice and confirms the importance of eliciting patients' preferences. 23 Decision analysis is usually used as a means of implementing evidence in practice, with preferences being elicited at a group level. 6 With the development and increasing sophistication of computer software, however, individual decision analysis is likely to be more common in the future.…”
Section: Comparison With Guidelinesmentioning
confidence: 99%